Peran Fleksibilitas Strategi dan Orientasi Pasar pada Peningkatan Inovasi dan Kinerja Usaha Kecil Menengah Sektor Industri Pengolahan Kota Malang - Sumiati, Sumiati (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2019)
The processing industry is a growing industry and accounts for around 1/5 of Indonesia's total Gross Domestic Product. This study analyzes the factors that influence the performance of SMEs in the manufacturing industry sector in Malang. Some variables such as internal and external environment, market orientation, are considered as important variables that influence the performance of SMEs, this study aims to examine the effect of market orientation and strategy flexibility on SME innovation and performance. This research is an explanatory study using a sample of 180 managers of processing industry SMEs in Malang. The data collected was analyzed using Structural Equation Modeling (SEM). Strategic flexibility and market orientation are found directly (direct effect) to affect innovation and company performance positively. In addition, proven innovation acts as a mediator in the influence of strategy flexibility and market orientation on company performance. Likewise, company performance has a role as a mediator for each strategy flexibility and market orientation towards innovation.